Giant vesicles: a powerful tool to reconstruct bacterial division assemblies in cell‐like compartments. (15th August 2013) - Jiménez, Mercedes; Martos, Ariadna; Cabré, Elisa J.; Raso, Ana; Rivas, Germán; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary The use of artificial lipid membranes, structured as giant unilamellar vesicles (GUVs), provides the opportunity to investigate membrane‐associated biological processes under defined experimental conditions. Due to their large size, they are uniquely adapted to investigate the properties and organization (in time and space) of macromolecular complexes incorporated in the vesicle interior by imaging and micro‐spectroscopic techniques. Experimental methods to produce giant vesicles and to encapsulate proteins inside them are here reviewed. Previous experimental work to reconstitute elements of the bacterial division machinery in these membrane‐like systems is summarized. Future challenges towards reconstructing minimal divisome assemblies in giant vesicles as cytomimetic containers are discussed.